Safety and efficacy of Yupingfeng granules in children with recurrent respiratory tract infection: A randomized clinical trial. Issue 2 (2nd June 2022) - Xu, Baoping; Li, Xinmin; Hu, Siyuan; Bao, Yixiao; Chen, Fengmei; Chen, Zhimin; Du, Yonggang; Liu, Enmei; Liu, Yufeng; Mou, Qinghui; Su, Baoling; Wang, Bo; et al.
ABSTRACT: Importance: Recurrent respiratory tract infection (RRTI) is common in children. Inappropriate RRTI treatment will lead to asthma and other diseases, thereby seriously affecting the growth and physical health of children. Immune function modulation can prevent and alleviate childhood RRTI. Yupingfeng (YPF), a patented traditional Chinese medicine (TCM), has immunomodulatory effects and is widely used in China to treat children with RRTI. Objective: To evaluate the safety and efficacy of YPF monotherapy in treating children with RRTI. Methods: This multicenter, randomized, double‐blind, double‐simulation, noninferiority clinical trial was conducted from January 2015 to August 2017, with an 8‐week treatment period and 52‐week follow‐up after the drug withdrawal. Children aged 2–6 years with RRTI meeting the inclusion and exclusion criteria were enrolled in 13 hospitals in China and divided randomly into three groups (2:2:1 ratio) to receive YPF, pidotimod, or placebo. The primary outcome was the proportion of RRTI returning to normal standard level during the follow‐up. The secondary outcomes were reduction in the number of RRTI recurrences, effect on clinical symptoms (in accord with TCM practice), effect per symptom, and safety. The trial was registered at the Chinese Clinical Trials Registry (www.chictr.org.cn ) under the unique identifier ChiCTR‐IPR‐15006847. Results: Three hundred and fifty‐one children were enrolled and randomly assigned to 3 groups; 124, 125, and 61 children in the YPF, pidotimod, and placebo groups, respectively, had completed the trial. During the follow‐up, the proportion of RRTI returning to normal standard level was 73.13%, 67.15%, and 38.81% with YPF, pidotimod, and placebo, respectively ( P < 0.0001). The proportion of cases who returned to normal standard level in the YPF group was 34.32% higher than that in the placebo group. The safety profile did not significantly differ among the groups. Interpretation: YPF granules were noninferior to the active control drug pidotimod oral solution for the treatment of RRTI in children, and were superior to placebo, with a high safety profile. Abstract : Recurrent respiratory tract infection (RRTI) is common in children. Inappropriate RRI treatment will lead to asthma, myocarditis, nephritis, and other diseases, thereby seriously affecting the growth and physical health of children. This multi‐center, randomized, double‐blind, double‐simulation, non‐inferiority clinical trial was conducted from January 2015 to August 2017, with a 52‐week follow‐up. Children with RRTI meeting the inclusion and exclusion criteria were enrolled in 13 hospitals in China and divided randomly into three groups (2:2:1 ratio). The primary outcome was the RRTI control rate during the follow‐up. The secondary outcomes were reduction in the number of RRTI recurrences, effect on clinical symptoms (in accord with TCM practice), effect per symptom, and safety. Three hundred and fifty‐one children were enrolled and randomly assigned to each group; 124, 125, and 61 children in the YPF, pidotimod, and placebo groups, respectively, had completed the trial. During the follow‐up, the RRTI control rate was 73.13%, 67.15%, and 38.81% with YPF, pidotimod, and placebo, respectively ( P < 0.0001). The RRTI control rate in the YPF group was 34% higher than that in the placebo group. The safety profile did not significantly differ among the groups. Overall, YPF can be used to treat children with RRTI and improve aversion to wind and spontaneous sweating, with a high safety profile.